(untitled) (SAARC Journal of Agriculture, 2020)
The study was undertaken to evaluate the quality of commercial beef cattle feed and feed ingredients which are available in Bangladesh. For this purpose, chemical analysis and in vitro digestibility (IVD) were estimated for nine commercial feeds and different feed ingredients which were collected from different regions. Chemical analysis of samples was carried out in triplicate for dry matter (DM), crude protein (CP), crude fiber (CF), ether extract (EE), ash, acid detergent fiber (ADF) and neutral detergent fiber (NDF) content. Metabolizable energy (ME) was calculated mathematically for feed samples by using standard formula. The analysis revealed the difference between the manufacturer’s claim and actual analyzed value. In commercial feeds DM content ranged from 90-92%. While CP content of commercial feeds was either lower or higher than the written value of feed industries. In Provita feed CP content (20.72%) was higher and Care feed had much lower CP content (7.54%) than written value. In vitro digestibility of DM in feed ingredients varied from 18.27 in straw to 75.77% in soybean meal. The fiber component (NDF and ADF) was negatively correlated with IVDMD and CP was positively correlated with IVDMD because fiber rich components were less digestible than the non-fibrous component (protein). Analysis of commercial feed samples revealed that the values claimed by the manufacturers are quite different from the actual analyzed values. This is a matter of concern and needs to be checked through better quality control measures by systematic feed analysis and ensure that manufacturers declare the true composition of the marketed feeds. SAARC J. Agri., 18(1): 197-208 (2020)